Randomised clinical trial: faecal microbiota transplantation versus autologous placebo administered via colonoscopy in irritable bowel syndrome. Issue 12 (28th April 2020) - Lahtinen, Perttu; Jalanka, Jonna; Hartikainen, Anna; Mattila, Eero; Hillilä, Markku; Punkkinen, Jari; Koskenpato, Jari; Anttila, Veli‐Jukka; Tillonen, Jyrki; Satokari, Reetta; Arkkila, Perttu
Summary: Background: Irritable bowel syndrome (IBS) has been associated with microbial dysbiosis. Aim: To investigate the efficacy of faecal microbiota transplantation (FMT) in the treatment of IBS. Methods: Forty‐nine IBS patients were randomised to receive autologous or allogenic FMT via colonoscopy. The primary endpoint was a sustained, minimum of 50‐point, reduction in the IBS Symptom Severity Score. The secondary outcomes were levels of anxiety and depression, changes in quality of life, gut microbiota and faecal water content as assessed with validated questionnaires, intestinal microbiota composition and stool dry weight. Results: The primary endpoint was not achieved in either group. However, there was a transient reduction in the mean IBS Symptom Severity Score in the FMT group at 12 weeks after treatment as compared to baseline ( P  = 0.01). The groups did not differ in the number of patients achieving clinical response at 12 weeks. In the FMT‐treated patients, microbial composition had changed to resemble that of the donor and the stool water content decreased significantly compared to baseline. The depression score decreased in patients with a reduction in IBS symptoms after FMT, but not in those placebo‐treated patients who experienced a reduction in IBS symptoms. Conclusions: FMT provided only a transient relief of symptoms, although it induced a sustained alteration in the microbiota of IBS patients. Therefore, FMT delivered by a single infusion via colonoscopy cannot be recommended as a treatment for IBS in clinical practice. ClinicalTrials.Org, Trial registration number: NCT03561519.